2020
DOI: 10.1186/s12886-020-1320-x
|View full text |Cite
|
Sign up to set email alerts
|

One-year natural course of corneal densitometry in high myopic patients after implantation of an implantable collamer lens (model V4c)

Abstract: Background: Corneal densitometry, which is also known as corneal backscattering, is a surrogate measure of corneal clarity. The purpose of the study was to investigate the changes in corneal densitometry (CD) after implanting an implantable collamer lens (ICL-V4c). Method: Twenty-six high myopic patients (aged 29.3 ± 6.6 years, 6 males and 20 females) who underwent ICL-V4c implantation were enrolled. Intraocular pressure (IOP), corneal topography, corneal densitometry, uncorrected distance visual acuity (UCDVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…They were published between 2012 and 2020. Table 1 presents a summary of these 35 clinical studies reporting data on the V4c ICL (Shimizu et al 2012; Alfonso et al 2013; Lisa et al 2015; Karandikar et al 2015; Shimizu et al.2016; Bhandari et al 2016; Eissa et al 2016; Chen et al 2016; Cao et al 2016a; Cao et al 2016b; Goukon et al 2017; Ganesh et al 2017; Rodríguez‐Una et al 2017; Pjano et al 2017; Kamiya et al 2017; Totsuka et al 2017; Fernández‐Vigo et al 2017; Kamiya et al 2018; Garcia‐de la Rosa et al, 2018; Fernández‐Vega‐Cueto et al 2018; Yan et al 2018; Kojima et al.2018; Li et al 2018; Takahashi et al 2018; Lee et al 2018a,b; Alfonso et al 2019; Rizk et al 2019; Zhu et al 2019; Niu et al 2019; Sachdev et al 2019; Martínez‐Plaza et al 2019; Wan et al 2019; Niu et al 2020; Chen et al 2020): authors, maximum follow‐up, number of eyes and patients included, sample mean age, preoperative SE, WTW, ACD, K, CCT and ICL size and power are shown. The outcomes of the 2904 eyes implanted with the V4c ICL model are described and analysed in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…They were published between 2012 and 2020. Table 1 presents a summary of these 35 clinical studies reporting data on the V4c ICL (Shimizu et al 2012; Alfonso et al 2013; Lisa et al 2015; Karandikar et al 2015; Shimizu et al.2016; Bhandari et al 2016; Eissa et al 2016; Chen et al 2016; Cao et al 2016a; Cao et al 2016b; Goukon et al 2017; Ganesh et al 2017; Rodríguez‐Una et al 2017; Pjano et al 2017; Kamiya et al 2017; Totsuka et al 2017; Fernández‐Vigo et al 2017; Kamiya et al 2018; Garcia‐de la Rosa et al, 2018; Fernández‐Vega‐Cueto et al 2018; Yan et al 2018; Kojima et al.2018; Li et al 2018; Takahashi et al 2018; Lee et al 2018a,b; Alfonso et al 2019; Rizk et al 2019; Zhu et al 2019; Niu et al 2019; Sachdev et al 2019; Martínez‐Plaza et al 2019; Wan et al 2019; Niu et al 2020; Chen et al 2020): authors, maximum follow‐up, number of eyes and patients included, sample mean age, preoperative SE, WTW, ACD, K, CCT and ICL size and power are shown. The outcomes of the 2904 eyes implanted with the V4c ICL model are described and analysed in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the ICL size, followed by horizontal STS, crystalline LT and vertical STS, significantly influenced 1-month postoperative vaulting. Previous studies have shown that the ciliary sulcus is vertically oval [ 37 39 ]. Because the ICL has a flat plate design and a certain width, the supporting points of the lens are located between the horizontal and vertical ciliary sulcus but closer to the horizontal position.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ICL size, followed by horizontal STS, crystalline LT and vertical STS, signi cantly in uenced 1-month postoperative vaulting. Previous studies have shown that the ciliary sulcus is vertically oval [37][38][39].…”
Section: Discussionmentioning
confidence: 94%